Elastoplastic stress–strain relationship of Si2N2O–Si3N4 ultrafine-grained ceramics based on microhardness test and finite element simulation. Issue 13 (September 2019) - Xi, Chenyang; Wang, Haotian; Zhai, He; Gu, Yongfei; Zhang, Chunxiang; Luo, Junting
Abstract: A method for obtaining the stress–strain relationship of ceramic materials was proposed on the basis of the relationship between the maximum load and the indentation size obtained by microhardness test. The microhardness testing process of Si2 N2 O–Si3 N4 ultrafine-grained ceramics was simulated using ABAQUS finite element software. The stress–strain relationship curve of the material was obtained by repeatedly modifying and comparing the experimental and simulation results. The hardness testing principle and elastic–plastic theory were comprehensively applied in this work in accordance with the geometrical characteristics of the Vickers diamond indenter. The theoretical formula for calculating the stress–strain relationship of hard and brittle materials using microhardness experimental data combined with finite element simulation was deduced. The elastic–plastic area division principle for calculating yield stress was proposed. The accuracy of the theoretical formula was verified by comparing the theoretical and simulation results.